KOMPOSISI VEGETASI HUTAN MANGROVE PANTAI AIR MATA PERMAI KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Padli, Zul; Muin, Abdurrani; M, Iskandar A (JURNAL HUTAN LESTARI, 2019)
The reaserch aimed to obtain data on the composition of mangrove forest vegetation in Air Mata Permai Beach Muara Pawan Subdistrict Ketapang District. The research was carried out on the mangrove forest in Air Mata Permai Beach, Muara Pawan Sub-District, Ketapang Regency in April-May with ± 1 month implementation time. The research method used in analyzing vegetation in the field is survey the grid line method. Lanes made is 5 (five) with a width of 10 meters and a length of 600 meters which is made perpendicular to the sea to the mainland. The results showed that in the mangrove forest Air Mata Permai Beach there were 16 types of vegetation with compositions consisting of Sonneratia alba, Avicennia alba, Rhizopora apiculata, Bruguiera gymnorrhiza, Exoecaria agallocha, Hibiscus tiliaceus, Lumnitzera littorea, Lumnitzera racemosa, Ceriops decandra, Xylocarpus granatum, Calophyllum inophyllum, Heritiera littoralis, Vitex pinnata, Acrostichum speciosum, Cerbera manghas and Nypa fructians. The dominant type of important value index (INP) is Rhizopora apiculata. The Species Diversity Index (H ') is included in the low category because the value of H'<1. The H 'value <1 indicates that the diversity of species on a transect or forest area is small or low and based on the results of the analysis of the type (e) Abundance Index data as a whole the range is 0,453-0,514, this states that the abundance between species is rather low or the individual wealth of each species is not evenly distributed.Keywords: Composition, Mangrove, Vegetation.